For the sake of agro-workers - Abd Razak, Dzulkifli (2005)
THE MIC President was last week reported as saying "this was a clear case of the poor being denied their rights" when referring to an incident involving a "land grab" (Malay Mail, April 22). Nowhere is such comment more relevant when it comes to the proposed lifting of the ban on paraquat, which is now being hotly contested by the pour — this time the plantation workers over their rights to better health. Dubbed as one of the "dirty dozen" pesticides, paraquat is widely used for weed control, at least before the ban, despite its deadly health effects. For example, paraquat warnings recognise that "it is very toxic by inhalation; toxic in contact with skin and if swallowed; irritating to eyes respiratory system and skin; and can be a serious threat to health.